PENGARUH PERTUMBUHAN VEGETATIF BEBERAPA VARIETAS KEDELAI HITAM DENGAN PEMBERIAN VERMIKOMPOS PADA TANAH MASAM - Chandri Lidya Putri Nasution; Luthfi Aziz Mahmud Siregar; Syafruddin Ilyas (Universitas Sumatera Utara, 2013)
ABSTRACTThe effect of Vegetative Growth on some Varieties of Black Soybeans with The Provision ofVermicompost on Acid Soils.Insufficient Black soybeans productiondomestic demand is a problemthat faced today. The addition of organic matter and using acid soils is one way that can be done toincrease the production of black soybean.The objective of the research was to know the effect ofvegetativegrowth on some varieties of black soybeans (Glycine max (L.) Merrill) with the provisionof vermicompost on acid soils. The experiment was conducted in the Public Land, Pasar I, TanjungSari, Medan, with altitude ± 25 meters above sea level from July to October 2012.Using a factorialrandomized block design with the first factor application of vermicompost (0, 0.8, 1.6 and 2.4kg/m²) and the second varieties (Detam-1, Detam-2, Cikuray, Merapi, Malikka) with threereplications. The result showed that the application of vermicompost insignificanly affected to all ofparametric in the research. The variety significantly affected the plant height at 2, 3, and 5 MST,andthe number of branches on the main stem. The combine between application of vermicompost andsoybean varieties were insignificanly to all of parametric in the research.Key word : soybean, acid soils, vermicompost, varieties